2013
DOI: 10.1155/2013/912807
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Problematic Mobile Phone Use: Development and Preliminary Psychometric Properties of the PUMP Scale

Abstract: This study aimed to develop and assess the psychometric properties of an English language measure of problematic mobile phone use. Participants were recruited from a university campus, health science center, and other public locations. The sample included 244 individuals (68.4% female) aged 18–75. Results supported a unidimensional factor structure for the 20-item self-report Problematic Use of Mobile Phones (PUMP) Scale. Internal consistency was excellent (α = 0.94). Strong correlations (r = .76, P < .001) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 15 publications
5
100
1
4
Order By: Relevance
“…The resulting fit values ( χ 2 /SD=1.997, GFI=0.90, AGFI=0.88, CFI=0.95, TLI=0.93, RMSEA=0.052, SRMR=0.0645) showed that these four dimensions are indeed components of a construct identified as problematic mobile phone use. Reviewing the literature for instruments developed to measure problematic mobile phone use, we find single-factor scales with 27 items by Bianchi and Phillips (4) or with 20 items by Merlo et al (23). The instrument developed by Yen et al (10) to determine problematic mobile phone use in adolescents is a two-factor construct containing a total of 12 items, seven of which are determining problematic mobile phone use and five that are dealing with functional impairment.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The resulting fit values ( χ 2 /SD=1.997, GFI=0.90, AGFI=0.88, CFI=0.95, TLI=0.93, RMSEA=0.052, SRMR=0.0645) showed that these four dimensions are indeed components of a construct identified as problematic mobile phone use. Reviewing the literature for instruments developed to measure problematic mobile phone use, we find single-factor scales with 27 items by Bianchi and Phillips (4) or with 20 items by Merlo et al (23). The instrument developed by Yen et al (10) to determine problematic mobile phone use in adolescents is a two-factor construct containing a total of 12 items, seven of which are determining problematic mobile phone use and five that are dealing with functional impairment.…”
Section: Discussionmentioning
confidence: 87%
“…In our data analysis, we first removed items 37 and 33, which were showing overlap. Next, 15 items with a factor loading below 0.50 (1,3,11,12,13,19,20,23,24,26,31,36,39,43,45) were eliminated from the scale. As can be seen in Table 1, the result of EFA, using principal component method and Varimax rotation, shows that the resulting scale has a 26-item 4-dimensional structure explaining 56.933% of the total variance; the item factor loadings with regard to this structure ranged between 0.61 and 0.82 in the deprivation (D) subdimension, between 0.53 and 0.74 in the adverse outcomes (AO) subdimension, between 0.51 and 0.69 in the control problem (CP) subdimension, and between 0.52 and 0.74 in the interaction avoidance (IA) subdimension.…”
Section: Validity Studies Exploratory Factor Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…(Lin et al, 2014 Smartphone; la COS y MPAI en los criterios diagnósticos de juego patológico del DSM-IV; la PMPUQ en criterios asociados a la impulsividad según la adaptación francesa de la escala UPPS; la TMDS ,la PCPU-Q, la SPUQ y la SAS en criterios del DSM-IV y DSM-VI-TR de abuso y dependencia de sustancias; la CERM y el TDM en criterios del DSM-IV para el abuso de sustancias y juego patológico; y la MPIQ en criterios del comportamiento adictivo de Brown (1997) y criterios propios del autor. El hecho de que los criterios de elaboración de las escalas de medición del uso del teléfono móvil sean distintos y que no posean fundamentos comunes, origina que no se puede demostrar científicamente que el móvil provoque adicción, pese a que algunos estudios realizados apunten a ello e indiquen que el tema merece una especial atención (Carbonell Sánchez, 2014;Merlo et al, 2013). La OMS, por su parte, también manifestó en un encuentro producido en Tokio en el año 2014, la alerta sobre las implicaciones en salud pública de los comportamientos excesivos asociados con el uso de tecnologías de la información y comunicación, incluyendo como no podía ser de otra manera, los Smartphones (Billieux et al, 2015).…”
Section: -Saps: Smartphone Addiction Proneness Scaleunclassified
“…Yen et al (2009) stated that the overuse of mobile phones can also be considered as a technology addiction; they established in a survey study, in which they based the addiction criteria included in DSM IV-TR, that 48.9% of participants had at least one of these criteria. Merlo, Stone, and Bibbey (2013) developed a scale based on DSM criteria and aimed to reveal the signs of problematic mobile phone use. In another study based upon DSM diagnostic criteria, the variables affecting mobile addiction were observed gathered under the factors of deprivation, lack of control, and tolerance (Choliz, 2012).…”
Section: Smartphone Addictionmentioning
confidence: 99%